2007
DOI: 10.1080/03067310701409317
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of fenitrothion residues in leaves and soil of vineyard after treatment with microencapsulate and emulsified formulations

Abstract: The rate of decline of fenitrothion residues was investigated in leaves and soil of vineyard over 2 months after treatment with two different kinds of commercial formulations: emulsifiable concentrate (EC) and microencapsulate (ME). Fenitrothion residues were determined with GC-NPD after acetone extraction of soil and leaves. The measured initial deposits in soil and leaves varied between 2.6 and 3.8 mg kg À1 and between 89 and 101 mg kg À1 , respectively. Fenitrothion residues in soil dropped at 0.1-0.2 mg kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…The recovery percentages were 85.69 for fenitrothion and 90.89 for thiobencarb in clay soil. These results confirmed by Likas and Tsiropoulos (2007) who found recovery of fenitrothion was 94±10% in soil by GC and Redondo et al (1994) who found the recovery of thibencarb in soil 63%. Similar carbamate recoveries were obtained from soil samples using liquid-liquid extraction with methylene chloride (Redondo et al, 1994).…”
Section: Recovery Of Tested Pesticidessupporting
confidence: 82%
See 2 more Smart Citations
“…The recovery percentages were 85.69 for fenitrothion and 90.89 for thiobencarb in clay soil. These results confirmed by Likas and Tsiropoulos (2007) who found recovery of fenitrothion was 94±10% in soil by GC and Redondo et al (1994) who found the recovery of thibencarb in soil 63%. Similar carbamate recoveries were obtained from soil samples using liquid-liquid extraction with methylene chloride (Redondo et al, 1994).…”
Section: Recovery Of Tested Pesticidessupporting
confidence: 82%
“…Fenitrothion degraded in upland and submerged soils with the half-life of less than 7 days and was of shorter persistence as compared with its half-life of 12-28 days under upland conditions and less than 14 days under submerged conditions found by Takimoto et al (1976). Fenitrothion half-lives in soil of about 17-21 days (Likas and Tsiropoulos, 2007). Studies carried out by Sundaram et al (1987) and Sundaram et al (1989) showed that the amount of fenitrothion deposited on soil dissipated quickly.…”
Section: Dissipation Kinetics Of Tested Pesticides In Soilmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar carbamate recoveries were obtained from soil samples using a traditional method involving liquid-liquid extraction (Leppert et al, 1983;Szeto and Sundaram, 1980). The recovery percentage of fenitrothion in soils was 94±10% (Likas and Tsiropoulos, 2007) also, in soil it was 98% (Roy et al, 1996). The non-extractable residue might be attributed to the formation of the soil-bound residue (Scheunert, 1992), its percentage ranged from 7 to 90% based on the applied pesticide (Khan and Dupont, 1987).…”
Section: Results and Discussion Recovery Of Tested Pesticides By Gc-msmentioning
confidence: 99%
“…To evaluate the decline of fenitrothion and thiobencarb residues in the studied soils, residue data should be subjected to statistical analysis to determine the statistical parameters that describe these processes, as proposed by Likas and Tsiropoulos (2007). Two methods were used to determine the best kinetic model for the degradation data, graphical and integral methods.…”
Section: Degradation Kinetics Of Tested Pesticides In Soilmentioning
confidence: 99%